Na cena do crime: intermídia, sensacionalismo e temporalidades anacrônicas nos contos de Valêncio Xavier e Boris Fausto - Leszczynski, Taynara (2021)
The main aim of this dissertation is to analyze the books Crimes à moda antiga (2004), by Valêncio Xavier and O crime da Galeria de Cristal (2019), by Boris Fausto, pointing out how Duchamp's ready-made technique, the concepts of intermedia, by Higgins and anachronism by Didi-Huberman are present in Brazilian detective short stories. In addition, we discuss some specific aspects about modernity, structure of short stories, narrator and detective story. We also observe how sensationalism prevails in national press through criminal news, especially fait divers.